Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Kolase Dengan Bahan Alam Sekitar Pada Anak Kelompok B DI TK ABA II Tombolo Kabupaten Gowa - hera wati (JKPD (Jurnal Kajian Pendidikan Dasar), 2022)
mproving fine motor skills through collage activities with natural materials for group B children at ABA II Kindergarten, Kuncio, Gowa Regency, 2021-2022 Academic Thesis of Teacher Training and Education, Universitas Muhammadiyah Makassar 2021.This study aims to improve children's fine motor skills through collage activities with natural materials for group B children in TK ABA II Kuncio, Gowa Regency for the academic year 2021-2022. This type of research is classroom action research (CAR). group B of 15 students in ABA II Kindergarten, Kuncio, Gowa Regency. This research is collaborative between researchers, teachers and school principals, data collection techniques using the results of their work, observations and documentation of classroom action research (CAR) were carried out in 2 cycles, each cycle carried out in 2 meetings. The procedure in this study has 4 stages, namely planning, implementing actions, observing or observing and reflecting. The data analyzed in the implementation of classroom action research are two types used, namely qualitative data and quantitative data, comparing the level of understanding and treatment achieved by children with the indicators applied. The results showed that the increase in fine motor skills through collage activities with natural materials around each child's fine motor cycle increased from 25.5% in the first cycle to 58.3% in the second cycle to 83.5%. collages of natural materials can improve the fine motor skills of students.Keywords: Children's fine motor skills in collage activities